PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN DAN DAMPAKNYA TERHADAP KEPERCAYAAN TERTANGGUNG ASURANSI KENDARAAN BERMOTOR PADA ASURANSI JASINDO (PERSERO) KANTOR CABANG PALU - Mulyana Zainal Mutakim; Syamsul Bachri; Wahyuningsih Wahyuningsih (Katalogis, 2018)
The aims of this research are: 1) to determine and analyze the influence of service quality on customers’ satisfaction; 2) to determine and analyze the influence of service quality on customers’ trust; 3) to determine and analyze the influence of customers’ satisfaction on trust. Type of study is explanatory in explaining the relationship between variables studied by involving 180 customers of four-wheel motor vehicles in Palu with probability sampling technique. Based on the result of SEM testing, the study find that; 1) service quality has positive and significant influence on customers’ satisfaction; 2) service quality has positive and significant influence on customers’ trust; 3) customers’ satisfaction has positive and significant influence on customers’ trust.